Partial genomic survival of cave bears in living brown bears - Barlow, Axel (Dr.); Cahill, James A.; Hartmann, Stefanie (Dr.); Theunert, Christoph; Xenikoudakis, Georgios; Gonzalez-Fortes, Gloria M.; Paijmans, Johanna L. A. (Dr.); Rabeder, Gernot; Frischauf, Christine; Garcia-Vazquez, Ana; Murtskhvaladze, Marine; Saarma, Urmas; et al. (Nature Ecology & Evolution, 2018)
Although many large mammal species went extinct at the end of the Pleistocene epoch, their DNA may persist due to past episodes of interspecies admixture. However, direct empirical evidence of the persistence of ancient alleles remains scarce. Here, we present multifold coverage genomic data from four Late Pleistocene cave bears (Ursus spelaeus complex) and show that cave bears hybridized with brown bears (Ursus arctos) during the Pleistocene. We develop an approach to assess both the directionality and relative timing of gene flow. We find that segments of cave bear DNA still persist in the genomes of living brown bears, with cave bears contributing 0.9 to 2.4% of the genomes of all brown bears investigated. Our results show that even though extinction is typically considered as absolute, following admixture, fragments of the gene pool of extinct species can survive for tens of thousands of years in the genomes of extant recipient species.